High Prevalence of Azithromycin-Resistant Neisseria gonorrhoeae Isolates With a Multidrug Resistance Phenotype in Fukuoka, Japan. Issue 6 (June 2015) - Tanaka, Masatoshi; Furuya, Ryusaburo; Irie, Shinichiro; Kanayama, Akiko; Kobayashi, Intetsu
Abstract : Background: The current guidelines recommend a combination of ceftriaxone and azithromycin as a first-line treatment of gonorrhea in the United States and Europe. Despite not being recommended as a first-line regimen in Japan, an oral 2-g dose of azithromycin did become available for gonococcal infections in 2009. Recently, the emergence of azithromycin-resistant Neisseria gonorrhoeae isolates has been reported in several countries, including Japan. Methods: Antimicrobial susceptibility testing was performed on a total of 677 clinical isolates of N. gonorrhoeae obtained from January 2010 to December 2013 in Fukuoka, Japan. A molecular analysis by N. gonorrhoeae multiantigen sequence typing was conducted on the azithromycin-resistant isolates. Results: The proportion of azithromycin-resistant isolates (minimum inhibitory concentration > 0.5 μg/mL) increased significantly from 1.8% in 2010 to 22.6% in 2013 ( P < 0.001). Among 50 azithromycin-resistant isolates, 30 (60%) exhibited a resistant phenotype to multiple drugs including cefixime. The 2 predominant sequence types (STs) identified by N. gonorrhoeae multiantigen sequence typing were ST6798 ( por allele 4033 and tbpB allele 110) and ST1407 ( por allele 908 and tbpB allele 110) at 40.0% (20/50) and 12.0% (6/50), respectively. There was a statistically significant increase of the proportion of ST6798 from 0% (0/19) in 2010–2012 to 64.5% (20/31) in 2013 ( P < 0.001). Conclusions: Over the previous 4 years, an increasing prevalence of azithromycin-resistant N. gonorrhoeae isolates with a multidrug-resistant phenotype was observed. Furthermore, the azithromycin-resistant isolates seemed to belong to 2 predominant STs. As a result, continued surveillance of gonococci resistant to antimicrobial agents, including azithromycin in Fukuoka, Japan, is necessary. Abstract : The prevalence of azithromycin-resistant Neisseria gonorrhoeae isolates with a multidrug-resistant phenotype has increased, which is mostly likely due to the emergence of the 2 predominant sequence types.